PENILAIAN DAYA TARIK DAN KARAKTERISTIK PENGUNJUNG PANTAI POLARIA DESA SUNGAI RUSAKECAMATAN SELAKAU KABUPATEN SAMBAS - Asrul, Asrul; Siahaan, Sarma; Azahra, Siva Devi (JURNAL HUTAN LESTARI, 2024)
Polaria beach which, is located in Sungai Rusa Village, Selakau District, Sambas Regency, has its own natural attraction value, namely the mangrove forest. The aim of the study was to determine the value of the attractiveness and characteristics of visitors to the Polaria beach tourist attraction, Sungai Rusa Village, Selakau District, Sambas Regency, using survey methods with observation techniques, interviews and using questionnaires. Sampling using accidental sampling technique. The assessment of Polaria beach attractions is carried out using the Scoring method using the ODTWA guidelines which have been modified according to the values/scores that have been determined for each criterion for assessing beach tourism attractiveness. The results of data analysis show that the attractiveness value of the Polaria beach tourist attraction is 869,76 (A) which means it is good for development. The charateristics of visitors who traveled to the coastal area of the Polaria beach tourist attractions were the most dominant at age (17-25 years) female and the everage visitor education was high school, while the highest visit rate was dominated by the area of origin, namely Sungai Rusa because it has a short distance only 2,5 km with a travel time of ± 5-10 minutes, and are dominated by student status, and the everage visitor is unmarried. Keywords: assessment attractiveness, beach, visitor characteristic. Abstrak Pantai Polaria yang berada di Desa Sungai Rusa Kecamatan Selakau Kabupaten Sambas memiliki nilai daya tarik alam tersendiri yaitu hutan mangrove. Tujuan penelitian untuk mengetahui nilai daya tarik dan karakteristik pengunjung objek wisata Pantai Polaria Desa Sungai Rusa Kecamatan Selakau Kabupaten Sambas, menggunakan metode survei dengan teknik observasi, wawancara dan menggunakan kuesioner. Pengambilan sampel menggunakan teknik accidental sampling. Penilaian objek wisata Pantai Polaria dilakukan dengan motode Skoring menggunakan pedoman ODTWA yang telah dimodifikasi sesuai dengan nilai/skor yang telah ditentukan masing-masing kriteria penilaian daya tarik wisata pantai. Hasil analisis data menunjukan bahwa nilai daya tarik objek wisata Pantai Polaria sebesar 869,76 (A) yang berarti baik untuk dikembangkan. Karakteristik pengunjung yang berwisata kekawasan pesisir objek wisata Pantai Polaria yang paling mendominasi pada usia (17-25 Tahun) berjenis kelamin perempuan dan pendidikan pengunjung rata-rata yaitu SMA, sedangakan tingkat kunjungan tertinggi berasal dari Sungai Rusa, karena memiliki jarak yang dekat hanya 2,5 km dengan waktu tempuh ± 5-10 menit, serta didominasi berstatus pelajar/mahasiswa, dan pengunjung rata-rata belum menikah. Kata kunci: karakteristik pengunjung, pantai, penilaian daya tarik